Robust dose planning objectives for mesorectal radiotherapy of early stage rectal cancer – A multicentre dose planning study. (September 2019) - Appelt, Ane L.; Kerkhof, Ellen M.; Nyvang, Lars; Harderwijk, Ernst C.; Abbott, Natalie L.; Teo, Mark; Peters, Femke P.; Kronborg, Camilla J.S.; Spindler, Karen-Lise G.; Sebag-Montefiore, David; Marijnen, Corrie A.M.; ,
Highlights: Mesorectal-only RT for early rectal cancer requires dedicated planning guidelines. A multi-centre study was conducted to identify planning objectives. Robust optimisation objectives for organs at risk are presented. Abstract: Background and purpose: Organ preservation strategies are increasingly being explored for early rectal cancer. This requires revision of target volumes according to disease stage, as well as new guidelines for treatment planning. We conducted an international, multicentre dose planning study to develop robust planning objectives for modern radiotherapy of a novel mesorectal-only target volume, as implemented in the STAR-TReC trial (NCT02945566). Materials and methods: The published literature was used to establish relevant dose levels for organ at risk (OAR) plan optimisation. Ten representative patients with early rectal cancer were identified. Treatment scans had mesorectal target volumes as well as bowel cavity, bladder and femoral heads outlined, and were circulated amongst the three participating institutions. Each institution produced plans for short course (SCRT, 5 × 5 Gy) and long course (LCRT, 25 × 2 Gy) treatment, using volumetric modulated arc therapy on different dose planning systems. Optimisation objectives for OARs were established by determining dose metric objectives achievable for ≥90% of plans. Results: Sixty plans, all fulfilling target coverage criteria, were produced. The planning results and literature review suggested optimisation objectives for SCRT: V 10Gy < 180 cm 3, V 18Gy < 110 cm 3, V 23Gy < 85 cm 3 for bowel cavity; V 21Gy < 15% and V 25Gy < 5% for bladder; and V 12.5Gy < 11% for femoral heads. Corresponding objectives for LCRT: V 20Gy < 180 cm 3, V 30Gy < 130 cm 3, V 45Gy < 90 cm 3 for bowel cavity; V 35Gy < 22% and V 50Gy < 7% for bladder; and V 25Gy < 15% for femoral heads. Constraints were validated across all three institutions. Conclusion: We utilized a multicentre planning study approach to develop robust planning objectives for mesorectal radiotherapy for early rectal cancer.